Recurrent Hyperkalemia During General Anesthesia in a Dog - Tong, Carissa W.; Balakrishnan, Anusha; Wynne, Rachel Matusow (Frontiers in Veterinary Science, 2020)
Objective: To describe the development of recurrent hyperkalemia under general anesthesia in a dog that underwent general anesthesia twice at two different hospitals within one month. The definitive underlying cause of the hyperkalemia remains unknown. Case Summary: A 11-year-old male neutered Rottweiler underwent general anesthesia twice at two different hospitals for ophthalmic surgery within one month and developed marked hyperkalemia on both occasions. The patient received similar drug protocols in both instances, including propofol, midazolam, non-depolarizing neuromuscular blocking agents, and isoflurane inhalant anesthetic. The patient showed ECG changes consistent with hyperkalemia during the first anesthetic event, but not the second. No other underlying cause of hyperkalemia was definitively identified. The patient responded to standard therapy for hyperkalemia on both occasions and serum potassium levels returned to normal. The patient was discharged from the hospital without further complications and post-operative rechecks showed persistently normal serum potassium levels. New or Unique Information Provided: Considering that there is a relationship between the development of severe hyperkalemia and propofol administration in people, it is possible that such a relationship exists in veterinary patients. However, numerous other disease conditions and medications can also lead to peri-operative hyperkalemia. Veterinary professionals should be aware that hyperkalemia can develop and remain to be an important differential diagnosis in bradycardic patients under anesthesia that are not responding to traditional therapies.